Policy and practical lessons learned regarding youth and NEETs in Slovenia - Bojnec, Štefan (Calitatea Vieții, 2021)
The article highlights the Slovenian strategies, institutions, policies, programmes, projects, and measures in tackling the NEETs, particularly the rural ones. The Youth Guarantee, and particularly active employment policy measures at a national level implemented via regional offices for employment work together to play a crucial role in bridging the gaps for the structurally and long-term unemployed in general, and especially for rural NEETs who are in transition from education and training to employment. National strategies and policies are supported by international programmes and projects. Amongst the success stories can be tentatively included the integration of the Roma population of at least one-cross-border area with geographical proximity to the neighbouring Styria region of Austria. Whilst the percentage of rural NEETs in Slovenia is modest, this does not mean an absence of the problems typical to this group i.e., less favourable personal, household, and/or other characteristics for the vulnerable, and economically and socially excluded rural NEETs. The hidden, unregistered NEETs (not participating in any programmes and policies) are at least as important as the registered ones. Both registered and unregistered NEETs are challenging issues in terms of their economic and social integration. To that end, it is necessary to provide general and specific opportunities for continued lifelong learning within the context of their personal, family, and social commitments: this will help to ensure their successful labour market and social integration, survival in the competitive labour market, quality of life by avoiding poverty risks, and sustainable rural development more broadly.